SPINE DEGENERATIVE DISEASES PATHOMORPHOLOGICAL BASIS AND A NEW APPROACH TO TREATMENT OF STRUCTURAL AND FUNCTIONAL TYPES OF THE NECK AND LINE - Mahkamov N.J.; Israilov R.I.; Narmatova D.M. (Scholar Express Journals, 2022)
The scientific work is devoted to the normal structure of the intervertebral disc, protrusion, pathomorphological changes and morphometric parameters of hernia and sequestered hernia. Scientific article The normal histological structure of the intervertebral disc was consecrated by studying histological and histochemical methods from cadaveric material. The main goal of the scientific work is to enrich information about the morphological changes and morphometric parameters of protrusion, hernias and sequestered hernias developing in the tissue structures of the intervertebral discs. The pathomorphological changes presented in the scientific article are considered by orthopedic traumatologists, neurosurgeons as the main fundamental data in the diagnosis, treatment and surgical procedures for these diseases.
Keywords: spine; symphysis; spinal disc; fibrous ring